THE 2024 FORMAL EU-US MENISCUS REHABILITATION CONSENSUS: AN ESSKA-AOSSM-AASPT INITIATIVE – PART II: Prevention, Non-Operative Treatment, and Return to Sport - Robert Prill; C. Benjamin Ma; Stephanie E. Wong; Philippe Beaufils; Juan Carlos Monllau; Elanna K. Arhos; Roland Becker; Francesco Della Villa; J. Brett Goodloe; James J. Irrgang; Jitka Klugarova; Emma L. Klosterman; et al. (International Journal of Sports Physical Therapy, 2025)
# Purpose Part-two of this consensus aimed to provide recommendations for the prevention of meniscus injuries, non-operative treatment of acute tears and degenerative lesions, return to sports, and patient-reported outcome measures. # Methods This consensus followed the European Society of Knee Surgery, Sports Traumatology and Arthroscopy (ESSKA) formal consensus methodology. For this combined ESSKA- American Orthopedic Society for Sports Medicine (AOSSM) - American Academy of Sports Physical Therapy (AASPT) initiative, 67 experts from 14 countries, including orthopedic surgeons and physiotherapists, were involved. The 26 Steering Group members established guiding questions, screened the existing evidence, and proposed statements, and provided Grades of recommendations. The 41 Rating Group members assessed the statements according to a Likert scale (1-9). Final documents were assessed by an international peer review group for geographical adaptability.